Analisis QoS Menggunakan Load Balancing Dengan Metode Nth Dan Failover Pada Mikrotik Di SMKN 1 PPU - Rahmadhani, Rizal; Burhandenny, Aji Ery; Wirawan, Adi Pandu; Suprihanto, Didit; Nugroho, Happy (ELECTROPS : Jurnal Ilmiah Teknik Elektro, 2024)
A fast and stable internet connection is the hope of all agencies and companies in their efforts to improve online performance. However, sometimes there are many obstacles to getting the desired connection quality, especially if we expect it from only 1 internet service provider. Adding an ISP in an effort to improve connection quality could be a solution if configured correctly. Load Balancing is a way to combine two network connections into one. The solution that can be taken to overcome this problem is by implementing the Nth method of load balancing and failover techniques which function to divide and balance the traffic load on the two existing connection lines and failover functions to back up if one of the ISPs goes down. The failover method test results showed that Indihome was 1 second and Indosat LTE was 2 seconds, with these results being categorized as very fast. For the Nth method load balancing results, the average Throughput results were 14472 kbps for 360p, 45501 kbps for 480p, and 27678 kbps for 720p. These results can be categorized as very good from the TIPHON standard, for an average delay of 87.25 ms for 360p, 340.6 ms for 480p and 375 ms for 720p from these results can be categorized as sufficient from the TIPHON standard, finally the average packet loss is 0.6% for 360p, 0.4% for 480p and 0.3% for 720p from these results can be categorized as very good by TIPHON standards.